Analysis of functional brain connectivity in patient with end-stage kidney disease undergoing peritoneal dialysis using functional near infrared spectroscopy - Chang Min Heo; Jiyae Yi; Dong Ah Lee; Kang Min Park; Yoo Jin Lee; Sihyung Park; Yang Wook Kim; Junghae Ko; Aryan Yohanes Djojo; Bong Soo Park (PLoS ONE, 2025)
Introduction Neurological complications are common in patients with end-stage kidney disease (ESKD). However, the mechanisms underlying neurological complications of ESKD are poorly understood. Research on brain connectivity in patients undergoing peritoneal dialysis (PD) is limited. In this study, we aimed to examine alterations in functional brain connectivity in patients with ESKD undergoing PD compared to the control group using functional near infrared spectroscopy (fNIRS). Methods We prospectively enrolled 20 patients with ESKD who had been receiving PD for more than 6 months and had no prior history of psychiatric or neurological diseases, along with 20 healthy controls. The fNIRS data were obtained using an NIRSIT Lite instrument. After processing all the data, we used Pearson correlation analysis to create a weighted connectivity matrix. Functional connectivity measures were derived from the connectivity matrix using graph theory. Functional connectivity measures were compared between the controls and patients with ESKD undergoing PD. Results The average degree, average strength, and small-worldness were significantly lower in patients with ESKD undergoing PD than in the controls (9.333 [8.000 ~ 11.433] vs. 12.733 [9.600 ~ 13.400], p = 0.030; 6.865 [4.768 ~ 7.560] vs. 8.432 [6.593 ~ 9.432], p = 0.036; 0.836 [0.724 ~ 0.900] vs. 0.949 [0.882 ~ 0.972], p = 0.025, respectively). Conclusion This study demonstrated significant alterations in functional brain connectivity in patients with ESKD undergoing PD, suggesting that functional brain connectivity is significantly reduced in patients with ESKD undergoing PD when compared with that in healthy controls.